giải PT a, sin(15độ -2x)=-1 b, sin2x+sin5x=0 c, cosx – 3 độ= $\frac{√2}{2}$ d, sin ²x +sin ²3x =1

Question

giải PT
a, sin(15độ -2x)=-1
b, sin2x+sin5x=0
c, cosx – 3 độ= $\frac{√2}{2}$
d, sin ²x +sin ²3x =1

in progress 0
Hailey 3 tháng 2021-09-20T01:00:04+00:00 1 Answers 4 views 0

Answers ( )

    0
    2021-09-20T01:01:44+00:00

    Đáp án:

    $\begin{array}{l}
    a)\sin \left( {{{15}^0} – 2x} \right) =  – 1\\
     \Rightarrow {15^0} – 2x =  – {90^0} + k{.360^0}\\
     \Rightarrow 2x = {105^0} – k{.360^0}\\
     \Rightarrow x = 52,{5^0} + k{.180^0}\\
    b)\sin 2x + \sin 5x = 0\\
     \Rightarrow sin2x =  – sin5x\\
     \Rightarrow sin2x = \sin \left( { – 5x} \right)\\
     \Rightarrow \left[ \begin{array}{l}
    2x =  – 5x + k2\pi \\
    2x = \pi  + 5x + k2\pi 
    \end{array} \right.\left( {k \in Z} \right)\\
     \Rightarrow \left[ \begin{array}{l}
    x = \dfrac{{k2\pi }}{7}\\
    x = \dfrac{{ – \pi }}{3} – \dfrac{{k2\pi }}{3}
    \end{array} \right.\left( {k \in Z} \right)\\
    c)\cos \left( {x – {3^0}} \right) = \dfrac{{\sqrt 2 }}{2}\\
     \Rightarrow \cos \left( {x – {3^0}} \right) = \cos {45^0}\\
     \Rightarrow \left[ \begin{array}{l}
    x – {3^0} = {45^0} + k{.360^0}\\
    x – {3^0} =  – {45^0} + k{.360^0}
    \end{array} \right.\left( {k \in Z} \right)\\
     \Rightarrow \left[ \begin{array}{l}
    x = {48^0} + k{.360^0}\\
    x =  – {42^0} + k{.360^0}
    \end{array} \right.\left( {k \in Z} \right)\\
    d){\sin ^2}x + {\sin ^2}3x = 1\\
     \Rightarrow {\sin ^2}x + {\sin ^2}3x = {\sin ^2}x + {\cos ^2}x\\
     \Rightarrow {\sin ^2}3x = {\cos ^2}x\\
     \Rightarrow \left[ \begin{array}{l}
    \sin 3x = \cos x\\
    \sin 3x =  – \cos x
    \end{array} \right. \Rightarrow \left[ \begin{array}{l}
    \sin 3x = \sin \left( {\dfrac{\pi }{2} – x} \right)\\
    \sin 3x = \sin \left( {x – \dfrac{\pi }{2}} \right)
    \end{array} \right.\\
     \Rightarrow \left[ \begin{array}{l}
    3x = \dfrac{\pi }{2} – x + k2\pi \\
    3x = \pi  – \dfrac{\pi }{2} + x + k2\pi \\
    3x = x – \dfrac{\pi }{2} + k2\pi \\
    3x = \pi  – x + \dfrac{\pi }{2} + k2\pi 
    \end{array} \right. \Rightarrow \left[ \begin{array}{l}
    x = \dfrac{\pi }{8} + \dfrac{{k\pi }}{2}\\
    x = \dfrac{\pi }{4} + k\pi \\
    x =  – \dfrac{\pi }{4} + k\pi \\
    x = \dfrac{{3\pi }}{8} + \dfrac{{k\pi }}{2}
    \end{array} \right.\\
     \Rightarrow \left[ \begin{array}{l}
    x = \dfrac{{k\pi }}{4}\\
    x = \dfrac{\pi }{8} + \dfrac{{k\pi }}{2}\\
    x = \dfrac{{3\pi }}{8} + \dfrac{{k\pi }}{2}
    \end{array} \right.\left( {k \in Z} \right)
    \end{array}$

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )